Management of Autoimmune Encephalitis with Refractory Status Epilepticus - Saputra, Rangga; Oktaliansah, Ezra (CoinReads Media Prima, 2025)
Introduction: Autoimmune encephalitis (AE) is a leading cause of non-infectious encephalitis. Its diagnosis remains challenging due to the often non-specific clinical presentation and difficulties in confirming antibody-negative cases. Comprehensive evaluation is essential to establish the diagnosis of AE. Case Report: We report a 25-year-old male presenting with decreased consciousness and seizures, accompanied by behavioral changes over the preceding 10 days. Electroencephalography (EEG) showed normal waveforms, and cerebrospinal fluid (CSF) analysis did not suggest infection. Brain CT scans were unremarkable, and serologic tests for herpes simplex virus (HSV) IgG and IgM were non-reactive. Notably, anti-NMDAR antibodies were positive. The patient was managed in the ICU with mechanical ventilation, sedated with propofol, and administered phenytoin for seizure control. Empirical treatment with acyclovir was given for 10 days, with no clinical improvement. First-line immunotherapy with methylprednisolone (1g/day for 5 days) was initiated but failed to produce neurological recovery. On day 14, CSF analysis indicated autoimmune etiology; plasma exchange was performed over three days, resulting in clinical improvement. Conclusion: Diagnosing and managing antibody-negative AE remains challenging. Clinical judgment, supported by the exclusion of differential diagnoses and the absence of characteristic radiological and immunological findings, can justify the initiation of immunosuppressive therapy or plasma exchange, which may lead to significant clinical improvement.